Which expression is equivalent to The equation

Accepted Solution

Answer: last option.Step-by-step explanation:  The negative exponent rules establishes the following: [tex]a^{-n}=\frac{1}{a^n}[/tex] The power to power property establishes:[tex](a^b)^c=a^{bc}[/tex] The product of powers property establishes that when you multiply two powers with equal base you must add the exponents. Applying the properties, you obtain the equivalent expression shown below: [tex](\frac{1}{x^2*x^6})^3=(\frac{1}{x^8})^3=\frac{1}{x^{24}}[/tex] Therefore the answer is the last option.